Migration of workers from Pará to Santa Catarina (Research, Society and Development, 2022)
The idea of this research emanates from the verification of the incisive presence of workers from Pará migrating to the state of Santa Catarina. The objective was to understand the migratory phenomenon for work. The methodology used books, articles and interviews with families and migrants. The result points to migration for work as a dramatic mechanism to over unemployment. In conclusion, people  from the state of Pará, in north of the country, are looking for work and better living in the state of Santa Catarina, Southern Brazil.